PERENCANAAN PENGGUNAAN LAHAN MELALUI PENDEKATAN PREDIKSI EROSI DAN KLASIFIKASI KEMAMPUAN LAHAN DI DAERAH ALIRAN SUNGAI KOLOH PASIRAN LOMBOK TIMUR - Sulastri Sulastri; I Wayan Sandi Adnyana; I Nyoman Merit (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2015)
Erosion is a form of land degradation is very serious in Koloh Pasiran watershed. This condition perceived more severe by the fact that the understanding of the process of saving the natural resources of forest, soil and water have not received maximum attention. This is evidenced by the presence of illegal logging, forest fires around the area of the watershed during the dry season and flooding during every rainy season. Therefore, the research conducted with the aim to: 1) determine the level of erosion and soil and water conservation planning in the Koloh Pasiran watershed, 2) determine the land capability class in Koloh Pasiran watershed and 3) to plan land use capability classes based on erosion rate. Observations and sampling of soil samples for prediction of erosion, soil conservation and classification approach according, planning based on common land unit. This land unit maps obtained from the land use maps overlay by slope, soil and land use maps done by estimating the magnitude of the erosion equation USLE (Universal Soil Loss Equation) of Wischmeier and Smit (1978). Determine land capability class with land capability classification approach according Arsyad (1989). Land use planning and soil and water conservation in addition to using USLE equation also uses land capability classification according Arsyad (1989). The results show the level of erosion prediction calculation slight to very severe erosion. Mixture of garden soil with a 2% slope erosion rates relatively slight. Dry land with a slope of 2% classified as severe erosion and the shrub land with a slope of 2-3% erosion classified as severe to very severe. While in secondary forest land and primary forests with a slope of 2-25% relatively slight erosion. Land capability class in Koloh Pasiran watershed can be classified into class IV (3 units of land), class V (5 units of land), class VI (1 unit of land) and VIII (2 units of land). The limiting factors are: (e) the slopes are steep and severe erosion rate and (s) low water holding capacity. Direction of land use for high density mixed garden with bench terrace with good construction, dry with good bench terrace construction and given a booster plants around the lip of land, shrub land used for community forestry, agroporestry and natural forests, while for secondary forests and forest maintained primary sustainability